Engineering inlet structures to enhance DNA capture into nanochannels in a polymer nanofluidic device produced via nanoimprint lithography - Jiahao Wu; Junseo Choi; Franklin I. Uba; Steven A. Soper; Sunggook Park (Micro and Nano Engineering, 2023)
Operating nanofluidic biosensors requires threading single molecules to be analyzed from microfluidic networks into nanostructures, mostly nanochannels or nanopores. Different inlet structures have been employed as a means of enhancing the number of the capture events into nanostructures. Here, we systematically investigated the effects of various engineered inlet structures formed at the micro/nanochannel interface on the capture of single λ-DNA molecules into the nanochannels. Different inlet geometries were evaluated and ranked in order of their effectiveness. Adding an inlet structure prior to a nanochannel effectively improved the DNA capture rate by 190–700% relative to that for the abrupt micro/nanochannel interface. The capture of DNA from the microchannel to various inlets was determined mainly by the capture volumes of the inlet structures and the geometrically modified electric field in the inlet structure. However, as the width of the inlet structure increased, the hydrodynamic flow existing in the microchannel negatively influenced the DNA capture by dragging some DNA molecules deep into the inlet structure back to the microchannel. Our results indicate that engineering inlet structures is an effective means of controlling the capture of DNA molecules into nanostructures, which is important for operation of nanofluidic biosensors.